Multivariate Mendelian randomization provides no evidence for causal associations among both psoriasis and psoriatic arthritis, and skin cancer - Yu, Nianzhou; Wang, Jiayi; Liu, Yuancheng; Guo, Yeye (Frontiers in Immunology, 2023)
Background Some retrospective studies reported that psoriasis (PsO) and psoriatic arthritis (PsA) may have been associated with an elevated risk of skin cancer. The causal associations among them remain unclear. Objectives To evaluate the causal association of among both PsO and PsA, and skin cancer. Methods We performed large-scale two-sample and Multivariate Mendelian randomization analyses to examine whether there is a causal relationship between PsO and PsA, and skin cancer, encompassing basal cell carcinoma (BCC), cutaneous squamous cell carcinoma (cSCC), and cutaneous melanoma (CM). Results Genetically predicted PsO, per log-odds ratio increase, showed no significant association with the risk of BCC, cSCC, and CM. The odds ratios (with corresponding 95% confidence intervals) for BCC, cSCC, and CM were 1.00 (0.99,1.01) (PIvw = 0.990), 0.94(0.89, 1.00) (PIvw = 0.065), and 0.99 (0.98, 1.01) (PIvw = 0.239), respectively. PsA showed a significant association with a decreased risk of BCC, with odds ratios (with corresponding 95% confidence intervals) of 1.00 (1.00, 1.00) (PIvw = 0.214) and 1.00 (1.00, 1.00) (PIvw = 0.477), respectively. Univariate analysis of the FinnGen database demonstrated PsA did exhibit a significant association with the decrease risk of BCC, with an odds ratio of 0.94(0.90,0.99) (PIvw = 0.016). However, this association disappeared after other risk factors were adjusted. Conclusions Our findings suggest no causal association between PsO and PsA and the genetic risk of skin cancer. Further observational studies are required to elucidate the relationship among PsO, PsA, and skin cancer.